Thin layer drying of ginger (Zingiber officinale) in a multi-rack type solar tunnel drier - JAYASHREE, E; VISVANATHAN, R (The Indian Journal of Agricultural Sciences, 2012)
Drying of ginger in a multi-rack type solar tunnel drier was studied. The drier consists of a UV-stabilized transparent plastic collector and a drying tunnel. Fresh ginger rhizomes were washed, peeled, spread in single layer in trays and dried from an initial moisture content of 594.01 to final moisture content of 9.89% (db). The temperature, relative humidity and solar intensity received under ambient and inside the solar tunnel drier were recorded. Mathematical modeling for thin layer drying showed that the diffusion approximation model best described the ‘over all’ drying process of ginger in a solar tunnel drier. The ‘over all’ effective moisture diffusivity of ginger in solar tunnel drier was 1.82 × 10-7 m2/s. The essential oil and oleoresin content of solar tunnel dried ginger were 2.0 and 4.5%, respectively and was at par with the quality of sun dried ginger. However, the microbial load of solar tunnel dried ginger was 6.12 log cfu/g where as for sun- dried ginger it was 6.69 log cfu/g and hence solar tunnel drying was considered superior.